(Meta)‐Analysis of Safety and Efficacy Following Edge‐to‐Edge Mitral Valve Repair Using the MitraClip System. (February 2015) - BAIL, DOROTHEE H.L.
<x xml:space="preserve">Abstract</x> Objectives The authors investigated safety and efficacy of the MitraClip‐System (MCS) using a systematic analysis. Background The safety and efficacy of the MCS continues to be debated, and randomized trials are still lacking. Method A systematic literature search was conducted using common medical and scientific databases. The following kinds of data were obtained: at baseline, 30 days, 6 and 12 month post‐procedure. For safety and efficacy mortality‐rate (survival), mitral regurgitation <2+ (MR), adverse event rate (AE), NYHA class and reoperation‐rate were documented. A meta‐analysis with quantitative summary was performed. Results Twenty‐six studies including 3821 patient's who were treated with MCS, were analyzed. Weighted mean age was 73.9 ± 2.3 years and LogEuroScore was 25.2 ± 6.0%. Post‐procedural MR<2+ was achieved in 86.4% and 66.3% of the patients were in NYHA class I/II within 30 days, AE‐rate was 18.3%, mortality‐rate was 2.8% and reoperation‐rate was 3.5%. Freedom from MR>3 + −4 was 80.2% (80.1%), from NYHA III/IV was 78.6% (66.1%) and freedom from death was 82.6% (87.8%) and from reoperation 95.6% (88.6%) at 6 and 12 month. Conclusion Based on the analysis of the current literature treatment with MCS is associated with good short‐term success and low mortality. MCS is safe and effective for patients with limited surgical options. The results are comparable with open mitral valve repair (oMVR) but patients are markedly older and have a higer risk profile than patients who undergo oMVR. Prospective randomized controlled trials are warranted to determine potential AEs, device durability and long‐term follow‐up. (J Interven Cardiol 2015;28:69–75)